A Final Note About Improving Needs Assessment Research and Practice. Issue 144 (December 2014) - Watkins, Ryan; Altschuld, James W.
Abstract: As with any field of inquiry and application, needs assessment is an evolving topic of research and practice. The theories, models, tools, and approaches are not idle targets. In this chapter, the authors explore the emerging trends and issues of the field, suggesting elements of an exciting future and the continuing call for more research that can improve practice. They include an examination of how technologies are expanding the methods employed in assessments and a discussion of how many of the challenges that have nagged at assessors for decades continue to limit our results. The future for needs assessments remains bright, but much work remains to be done in order for needs assessment to mature as a field.